2018
DOI: 10.1186/s12875-018-0725-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self-efficacy, self-care behaviour and glycaemic control among patients with type 2 diabetes mellitus in the Malaysian primary care setting

Abstract: BackgroundSelf-efficacy has been shown to be positively correlated with self-care behaviour and glycaemic control among patients with type 2 diabetes mellitus. However, such evidence is lacking in the Malaysian primary care setting. The objectives of this study were to i) determine the levels of self-efficacy, self-care behaviour and glycaemic control among patients with type 2 diabetes mellitus in the Malaysian primary care setting ii) determine the relationship between self-efficacy, self-care behaviour and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
57
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 16 publications
9
57
1
8
Order By: Relevance
“…Self‐efficacy had moderate association with self‐management (Tharek et al., 2018). The relationship between diabetes management self‐efficacy and DSM is significant, regardless of the patient's race or health literacy (Sarkar, Fisher, & Schillinger, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐efficacy had moderate association with self‐management (Tharek et al., 2018). The relationship between diabetes management self‐efficacy and DSM is significant, regardless of the patient's race or health literacy (Sarkar, Fisher, & Schillinger, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There were several known significant factors associated with glycaemic control, as repetitively described in other studies. The factors include age, sex, race, duration of diabetes, educational level and employment status [12][13][14][15]28]. In this study, factors including age, sex, race and duration of diabetes were found significantly associated with glycaemic control, thus were controlled in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…There are several significant factors associated with glycaemic control which has been revealed by many studies such as age, sex, duration of diabetes and educational level [4,[12][13][14][15][16]. However, to the best of our knowledge, there is scarce local evidence that examines the relationship between FDC implementation and doctor-patient interaction satisfaction towards glycaemic control among T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Neste estudo, o monitoramento da glicemia obteve precárias médias de adesão tanto no que se refere à sua prática como à frequência desejável. Este resultado é comparável ao de um estudo realizado na Malásia (18) .…”
Section: Introdução Métodounclassified